An experimental investigation into active structural acoustic cloaking of a flexible cylinder. (15th December 2020) - House, Charlie; Cheer, Jordan; Daley, Steve
Abstract: The ability to acoustically cloak an object, effectively making the object acoustically invisible to an outside observer, is of interest in many applications where the presence of an object has an undesirable impact on the sound-field. If a suitable disturbance signal can be measured, an active control system can be used to directly minimise the scattered acoustic pressure, which fully characterises the presence of the body. In this paper, a broadband feedforward active control system is used to minimise the scattered acoustic pressure at a far-field microphone array using an array of structural control sources affixed to the flexible scattering body. The performance of this system is assessed using measured data corresponding to a hollow cylindrical shell subject to an incident acoustic field, and the causality of the control filters is investigated. It is shown that the practical causality constraint limits the performance of the active cloak at lower frequencies, but the causally constrained controller is able to achieve approximately 10 dB of attenuation in the far-field scattered acoustic power, using an array of 9 control actuators. The influence that the number of control actuators has on the attenuation performance is investigated, the practicability of the system is discussed, and a number of potential implementation challenges are identified, including the increased level of structural vibration caused by the active structural acoustic cloaking system.